NUSHÅªZ SUAMI-ISTRI DAN SOLUSINYA: Studi TafsÄ«r al-RÄzÄ« - Zuhrah, Fatimah (Al-Ahkam, 2016)
NushÅ«z means a wife do anything against her husband for no reason that can be accepted by Islamic law (wife nushÅ«z), or husband does not carry out its obligations as stipulated in Islamic law (husband nushÅ«z). This article intends to analyze the concept of nushÅ«z according to Islamic law in the perspective of Fakhr al-DÄ«n al- RÄzÄ« in his Qurâ€™anic commentary (tafsÄ«r). It also discussed about the solutions of nushÅ«z according to the Qurâ€™an. Based on the study of sura al-Nisa verse: 34, 35, and 128 that nushÅ«z can be done even by the wife or the husband. When problems of nushÅ«z already potentially shiqÄq, it is advisable to appoint a á¸¥akam (mediator), both from husbandâ€™s families and wife's families.NushÅ«z berarti seorang istri melakukan perbuatan yang menentang suami tanpa alasan yang dapat diterima oleh hukum Islam, atau sebaiknya suami tidak menjalankan kewajibannya sebagaimana ketentuan hukum Islam. Artikel ini bermaksud untuk menganalisis konsep nushÅ«z menurut hukum Islam dalam perspektif Fakhr al-DÄ«n al-RÄzÄ« dalam kitab tafsirnya. Selain itu juga dibahas tentang bagaimana tawaran solusi nushÅ«z menurut al-Qurâ€™an berdasarkan kajian terhadap surat al-NisÄâ€™ ayat 34, 35, dan 128 bahwa nushÅ«z bisa dilakukan oleh istri maupun suami. Ketika permasalahan nushÅ«zsudah mengkhawatirkan sehingga berpotensi shiqÄq, maka dianjurkan untuk mengangkat seorang á¸¥akam (mediator), baik dari keluarga suami maupun keluarga istri.